Dispersion characteristics of dust pollutant in a typical coal roadway under an auxiliary ventilation system. (1st December 2020) - Geng, Fan; Gui, Changgeng; Teng, Haixu; Tang, Junhua; Niu, Hongwei; Zhou, Fubao; Liu, Chun; Hu, Shuda; Li, Shihang
Abstract: To control dust pollutant efficiently for cleaner production, the present study investigated the dispersion characteristics of dust pollutant in a typical coal roadway under an auxiliary ventilation system. First, the dust particles with the air flow were investigated successively via the Euler-Euler and the Euler-Lagrange methods. Meanwhile, each dust particle was traced, and the particle collisions were considered via the hard-sphere model and the direct simulation Monte Carlo method. Then the bulk movements of dust particles were simulated after certain validations with the related the field measurement results, and dust distribution were explored under main influence factors, like the particle size and the initial supply air velocity. The present study indicated that the circumfluence occurs mainly with the finer and the fine dust particles (<20 μm), which also contribute in dust suspension. Approximately 50% or more of the total suspended particles are particulate matter that that less than 10 μm (PM10). The relatively bigger particles (>40–60 μm) mainly settle down on the return air side. Dust separation and the layering distribution of different sized particles are more obvious when the initial supply air velocity is higher. The sedimentary and the suspended particles presented by the quantity overtime all follow the logistic function, including PM10 and PM2.5. The present results on dust pollutant deepen the understanding of dust dispersion in the confined space and provide helpful guidance on effective dust control methods for cleaner production. Graphical abstract: Image 1 Highlights: Space-time evolution of dust pollutant dispersion was visually analyzed at particle-scale. Circumfluence mainly with fine dust (<20 μm) directly influences dust distribution. Approximately 50% or more of the total suspended particles are PM10. Logistic function can predict dust quantity for the sedimentary and the suspension.